Atypical depression: selection criteria, systematics, approaches to therapy - N. A. Tyuvina; M. S. Verbitskaya; A. E. Stolyarova (Неврология, нейропсихиатрия, психосоматика, 2020)
The paper reviews Russian and foreign literature on atypical depression (AtD). It sets forth the historical aspects of identifying AtD among other depressive disorders: the authors have traced the path from depression with individual atypical manifestations to a syndrome with a clearly defined pattern and inclusion criteria in the international DSM-4 and DSM-5 classifications. The paper gives epidemiological indicators and shows their diversity due to various approaches to the determination and clinical assessment of AtD. It analyzes the results of studying AtD in the presence of various affective disorders, such as recurrent depressive disorder, bipolar affective disorder, and psychogenic depression, and notes their heterogeneity in both symptoms and genesis. The authors present approaches to treating AtD and the results of investigating drug (antidepressant) and non-drug (cognitive-behavioral psychotherapy, increased physical activity therapy) treatments.